Effect of Pre-milling Treatments on Green Gram Dhal Recovery - WANI, S Kshitija; JHA, S K; SINGH, AMAR; SHRIVASTAVA, R; JHA, G K; SINHA, J P (Journal of Agricultural Engineering, 2012)
Effect of oil and thermal treatments on milling quality of green gram was studied at 8 to 12% moisture content (w.b) with 2.40 to 4.00 g.kg-1 oil for treatment and holding time of 5 to 10 h, thermal treatment at temperature of 80 to 120Â°C and roasting duration of 1 to 5 min. These pretreatments showed dhal recovery of 70.01 to 74.93% in case of oil treatment, and 71.18 to 78.12% in case of thermal treatment as against 61.19 to 65.64% without any pretreatment. Optimum conditions for oil treatment for maximum dhal recovery were 10.26% (w.b), oil quantity of 3.17 g.kg-1 and holding for 7.72 h, roasting for 2.86 min at temperature of 99.24Â°C and 10.25% moisture content (w.b) for thermal treatment of green gram.